STUDENTS’ PERCEPTIONS OF MATHEMATICS AS A “FRIGHTENING” SUBJECT - Andi Mulawakkan Firdaus; Herwandi Sape (Jurnal Penalaran dan Riset Matematika, 2025)
This study aims to explore students’ perceptions of mathematics as a “frightening” subject and to identify the factors influencing such perceptions. The research was conducted in senior high schools across Maros Regency, South Sulawesi, using a mixed-methods approach. Data were collected through a Likert-scale questionnaire to quantitatively measure students’ perceptions, and semi-structured interviews with students and teachers to gather qualitative insights. The findings reveal that the majority of students hold negative perceptions of mathematics, characterized by anxiety, stress, and a lack of self-confidence in learning. Contributing factors include monotonous teaching methods, pressure from teachers and the school environment, and unpleasant learning experiences. Teachers also acknowledged challenges in changing students’ perceptions due to curriculum demands and limited instructional time. This study recommends the implementation of more contextual, enjoyable, and student-centered teaching approaches to transform negative perceptions into positive ones. These findings provide valuable input for policymakers, educators, and curriculum developers in designing mathematics instruction that is more student-friendly and focused on meaningful learning experiences.